2003
DOI: 10.1295/polymj.35.88
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Hetero Telechelic Hyperbranched Polyether. Anionic Ring-Opening Polymerization of 3-Ethyl-3-(hydroxymethyl)oxetane Using Potassium tert-Butoxide as an Initiator

Abstract: KEY WORDSHetero Telechelic Hyperbranched / Anionic Polymerization / Polyethers / 3-Ethyl-3-(hydroxymethyl)oxetane / Oxetanes with 4-membered ring are polymerized exclusively with cationic initiators, due to high basicity. 1 Vandenberg et al. reported that cationic ring-opening polymerization of 3-ethyl-3-(hydroxymethyl)-oxetane (EHO) in the presence of aluminum complexes as cationic initiators produced linear polymers with high crystallinity and no glass transition temperature. 2, 3 Hyperbranched polymers by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…88,89 They obtained polymers with molecular weights up to 4100 g mol À1 in good yields, but with broad polydispersities (M w /M n ¼ 4.0-5.5). The DB was comparatively low with values between 16% and 27%.…”
Section: Highlightmentioning
confidence: 99%
“…88,89 They obtained polymers with molecular weights up to 4100 g mol À1 in good yields, but with broad polydispersities (M w /M n ¼ 4.0-5.5). The DB was comparatively low with values between 16% and 27%.…”
Section: Highlightmentioning
confidence: 99%
“…18 In this paper, we examined the synthesis of hyperbranched poly(ether) by the anionic polymerization of BHO, containing two hydroxyl groups (Scheme 2).…”
Section: Anionic Ring-opening Polymerization Of Bhomentioning
confidence: 99%
“…[13][14][15][16][17] More recently, we reported a new anionic ringopening polymerization of EHO and 3-methyl-3-hydroxymethyloxetane (MHO) containing hydroxyl groups using potassium tert-butoxide (t-BuOK) and 18-crown-6-ether (18-C-6), affording the hyperbranched polyether containing an oxetanyl group and many hydroxyl groups at the end (Scheme 1). 18,19 Furthermore, we achieved the synthesis of a pseudo dendritic polymer with many pendant hydroxyl groups by the cationic ring-opening polymerization of the poly(EHO) derivative. 19 These synthesized polymers poly(EHO), poly(MHO), and pseudo dendritic polymers are expected as useful functional materials, because they have many hydroxyl groups at the ends.…”
mentioning
confidence: 99%
“…These reactions can be applied practically to the polyadditions of bis(oxetane)s with above reagents such as diacyl chlorides, 14-17 phosphonyl dichlorides, 8 active diesters, 18,19 dicarboxylic acids, 10 bisphenols, 11,12 and dithiols 13 to afford corresponding polymers with high molecular weights. Recently, we also found that an anionic ring-opening polymerization of 2-(hydroxymethyl)oxetanes produced corresponding hyperbranched poly(ether)s containing one terminal oxetanyl groups and many pendant primary hydroxy groups using the complex of potassium t-buthoxide with crown ether as a catalyst system, [20][21][22] and an anionic ring-opening alternating copolymerization 23 of oxetanes with cyclic carboxylic anhydrides using certain quaternary onium salts as catalysts.The above reaction systems of oxetane compounds and the oxetane polymers prepared by the reactions seem to have great possibility as an important key technology in coatings and electronics fields, and polymer industry in general.Meanwhile, hyperbranched polymers (HBPs) have recently attracted a great deal of attention as one of the dendritic macromolecules, which have lower viscosity, good solubility and many reactive terminal groups compared with the corresponding linear ones. 24 There are many synthetic methods for the preparation of the HBPs, such as vinyl polymerization 25 and ring-opening polymerization 26 accompanying suitable chain transfer reaction.…”
mentioning
confidence: 99%
“…These reactions can be applied practically to the polyadditions of bis(oxetane)s with above reagents such as diacyl chlorides, [14][15][16][17] phosphonyl dichlorides, 8 active diesters, 18,19 dicarboxylic acids, 10 bisphenols, 11,12 and dithiols 13 to afford corresponding polymers with high molecular weights. Recently, we also found that an anionic ring-opening polymerization of 2-(hydroxymethyl)oxetanes produced corresponding hyperbranched poly(ether)s containing one terminal oxetanyl groups and many pendant primary hydroxy groups using the complex of potassium t-buthoxide with crown ether as a catalyst system, [20][21][22] and an anionic ring-opening alternating copolymerization 23 of oxetanes with cyclic carboxylic anhydrides using certain quaternary onium salts as catalysts.…”
mentioning
confidence: 99%